The Impact of Smartphone Addiction on Sleep Quality among Elementary School Teacher Education Students (PGSD) - Ginting, Nurul Agustina; Sulistianingsih, Dewi; Alim, Jesi Alexander; Ulya, Zakiah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of digital technology has made smartphones an inseparable part of college students' lives. This study aims to describe the smartphone usage profile of Elementary School Teacher Education (PGSD) students and its impact on concentration, sleep quality, daily habits, and academic activities. The research method used was descriptive quantitative, with 57 students as respondents. Data were collected through a Likert-based questionnaire and analyzed descriptively using frequency distributions and percentages. The results showed that the majority of students (89.5%) used smartphones before bed, with the highest usage duration being 4–8 hours per day (38.6%). Sixty-six percent of respondents admitted to using their smartphones longer than intended, 56% felt distracted by notifications, 47% experienced decreased sleep quality, and 58% habitually used their smartphones while eating or taking breaks. Furthermore, 38% of respondents stated that their academic activities were disrupted by smartphone use. In conclusion, excessive smartphone use has become a habit that significantly impacts students' sleep quality, concentration, and daily activities. Therefore, students need to increase their awareness of managing their smartphone usage time to maximize benefits and minimize negative impacts.